The Role of Commitment Organization as Mediation Influence Leadership Transformational and Work-Life Balance on the Performance of Sales General Employees of PT. Bank Mandiri (Persero) Tbk Cluster Situbondo - Muhamad Sulton; Raden Andi Sularso; Dewi Prihatini (Jurnal Ilmu Manajemen Advantage, 2023)
Employee is part in a company, besides it's also in the environment employee there is a leader or someone who can set and carry direction coordination of goals organization. This study aims to test and analyze role commitment organization as mediation influence leadership transformational and work life balance towards performance general sales employees of PT. Bank Mandiri (Persero) Tbk Situbondo Cluster. This research includes in approach quantitatively using questionnaire as tool data collection from respondent. Respondents in this study were 52 sales employees using sample saturated. Method analysis use Partial Least Square Equation Model (SEM-PLS) structure using smartPLS 3.0 software. Research results shows that leadership transformational own no influence significant to commitment organization and performance employees, while the work life balance has significant influence to commitment organization and performance employees, as well as commitment organization own significant influence to performance employee. Commitment organization No can role as mediation from leadership transformational to performance, however commitment organization can role as mediation Partial from work life balance to performance employee.